SWOT ANALYSIS OF THE IMPLEMENTATION OF NO SMOKING AREA AT UIN ALAUDDIN MAKASSAR - Wijaya, Dian Rezki (Homes Journal: Hospital Management Studies Journal, 2023)
One of the focuses of the No Smoking Area is based on the lawHealth and Makassar City Regional Regulation Number 4 of 2013 is a place of teaching and learning process. This rule has not been implemented yet State Islamic University Alauddin Makassar, the reality shows that there are still lecturers, staff, and students who still smoke in campus area. So, this research was conducted to find out how SWOT Analysis of the Implementation of No Smoking Areas at UIN Alauddin Makassar.This research uses a qualitative method with a case study design. The number of informants was 26 people consisting of Vice Chancellor III, Dean, Lecturers, Employees, Students. Results research shows that there is strength in implementing a Smoking Free Area at UIN Alauddin Makassar namely there are rules of conduct regulated in the UIN Alauddin Student Pocket Book Makassar regarding the prohibition of smoking in buildings or faculties. However, there are Weaknesses that are owned by the Academic Community namely the existence of lecturers, employees and students who smoke in the building area or faculty so that it can disturb the people around him. As for in terms of Opportunities that there are Anti-Smoking Alauddin Makassar which can be used as empowerment and relationship relationships built with external institutions, namely Hasanuddin Contact which can work together to implement a No-Smoking Area at UIN Alauddin Makassar. On the other hand, that there is a threat that will generated as a disagreement, can creates a contradiction to active smokers if no room is provided specifically for smoking so it could be a demonstration to sue that matter.